2023
DOI: 10.1115/1.4062337
|View full text |Cite
|
Sign up to set email alerts
|

SW-SiStA2: A New-Generation Semi-Wearable Device for Sit-to-Stand Assistance

Abstract: Mobility impairment is a major problem that affects the quality of life of numerous older adults. With impaired mobility, such individuals usually have significant difficulty in standing up from a seated position, and thus often suffer from the lack of physical activities in their daily life. To address this problem, the authors present a new assistive device, namely Semi-Wearable Sit-to-Stand Assist Generation-2 (SW-SiStA2), in this paper. Similar to the original (first generation) SW-SiStA, this novel semi-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…SW-SiStA2 is an STS movement assistive device characterized by quick donning and easy doffing, using air springs as the power source to assist the lower limbs. Experiments have shown that this device significantly aids in promoting the standing action, reducing muscle activation by up to 28% [18]. Purwar et al have designed a new type of six-bar mechanism assistive device for the elderly that aids in standing up and walking.…”
Section: Introductionmentioning
confidence: 99%
“…SW-SiStA2 is an STS movement assistive device characterized by quick donning and easy doffing, using air springs as the power source to assist the lower limbs. Experiments have shown that this device significantly aids in promoting the standing action, reducing muscle activation by up to 28% [18]. Purwar et al have designed a new type of six-bar mechanism assistive device for the elderly that aids in standing up and walking.…”
Section: Introductionmentioning
confidence: 99%